1988
DOI: 10.1002/eji.1830180406
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction through cd4 receptors: stimulatory vs. inhibitory activity is regulated by cd4 proximity to the cd31t cell receptor

Abstract: The binding of antibody to the CD4 molecule inhibits mobilization of cytoplasmic free calcium ([Ca2+]i) in response to CD3 cross-linking on resting T cells. Similarly, when CD3 and CD4 are independently and simultaneously cross-linked, calcium mobilization is inhibited when compared to that induced by cross-linking CD3 alone. In contrast, when anti-CD4 and anti-CD3 are cross-linked together, calcium mobilization is substantially higher than from CD3 cross-linking alone. A heteroconjugate consisting of covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(79 citation statements)
references
References 45 publications
2
75
0
2
Order By: Relevance
“…Evidence for an intercellular binding of CD4 to the class II MHC has been obtained (19). On the other hand, there are several lines of evidence suggesting that CD4 may interact with the TCR or the TCR-T3 complex within the Th-cell membrane (20)(21)(22)(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for an intercellular binding of CD4 to the class II MHC has been obtained (19). On the other hand, there are several lines of evidence suggesting that CD4 may interact with the TCR or the TCR-T3 complex within the Th-cell membrane (20)(21)(22)(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…Antibody crosslinking of the T-cell receptor by using anti-CD3 antibodies or cross-linking of the CD4 cell surface glycoprotein has been previously shown to result in phosphorylation and activation of p56Ick (1,47,49,51). Simultaneous cross-linking of both the T-cell receptor and the CD4 glycoprotein has been shown to enhance some parameters of T-cell activation compared with cross-linking of either CD3 or CD4 alone (29,33). Others have demonstrated an increase in p56 ck-associated PI3K activity in T cells following T-cell receptor activation (44).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo, the impact of CD4 and CD8 on TCR signaling was shown to be, at least in part, through binding nonpolymorphic regions of MHC class II or class I, allowing CD4 and CD8 to act as auxiliary binders to tighten the key interaction between the TCR and peptide within the binding pocket of MHC. However, a number of investigators speculated that, in addition to serving as a means to stabilize interactions, the coreceptors might participate directly in signal transduction, either by initiating unique signals or by affecting signals known to be driven by TCR engagement (13)(14)(15). Although many studies using Abs directed against either CD4 or CD8 suggested that these proteins might transduce signals, it was not until the two Pillars of Immunology papers reprinted in this issue of The Journal of Immunology (16,17) were published that a molecular basis for this action could be proposed.…”
Section: Multiple Roles Of Cd4 and Cd8 In T Cell Activationmentioning
confidence: 99%